2011
DOI: 10.1055/s-0031-1273719
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Prognostic Value of Horner Syndrome in Perinatal Brachial Plexus Palsy

Abstract: The aim of this study was to evaluate the prognostic value of Horner syndrome as an indicator of preganglionic injuries of the lower part of the brachial plexus. The study investigated 18 cases of children with perinatal brachial plexus injury and coexistent Horner syndrome. The following data sets were analyzed: the degree of severity of the brachial plexus injury, the results of imaging examinations, the intraoperative view, the kind of operative treatment and the resultant hand function. On the basis of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The presence of ptosis (drooping eyelid), miosis (pupil constriction) and/or anhidrosis (dry eye) are signs of unilateral Horner’s syndrome or injury to the sympathetic trunk; which is linked to injury in the lower roots of the brachial plexus. 91 Difficulty with oxygenation, feeding and asymmetric chest expansion are symptoms of partial denervation to the diaphragm and warrant further screening for phrenic nerve injury (nerves C3, C4, and C5). 92 Concerns raised during observations require further assessment.…”
Section: Assessment: Infantmentioning
confidence: 99%
“…The presence of ptosis (drooping eyelid), miosis (pupil constriction) and/or anhidrosis (dry eye) are signs of unilateral Horner’s syndrome or injury to the sympathetic trunk; which is linked to injury in the lower roots of the brachial plexus. 91 Difficulty with oxygenation, feeding and asymmetric chest expansion are symptoms of partial denervation to the diaphragm and warrant further screening for phrenic nerve injury (nerves C3, C4, and C5). 92 Concerns raised during observations require further assessment.…”
Section: Assessment: Infantmentioning
confidence: 99%
“…They suspected that some sympathetic preganglionic fibres to the superior cervical ganglion may exit the cord by means of the ventral root of the C7 spinal nerve in neonates. Gosk et al (2011) reported that spinal root avulsion and suspicious avulsion was observed in only 10 of 17 (59%) cases with Horner syndrome. Huang et al (2008) investigated 12 fresh infant and 12 adult cadavers and found that the white rami communicantes exited via the C7, C8 and T1 roots in the infant, whereas these white rami communicantes were not found to join the stellate ganglion through the C7 ventral root in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Chuang et al (1998) reported that 19% (46 of 242) of neonates with NBPP had a concurrent Horner syndrome. Gosk et al (2011) reported that 37% (17 of 46) neonates and Al-Qattan et al 2000reported that 50% (24 of 48) neonates with total-type palsy had a concurrent Horner syndrome. Jeffery et al (1998) indicated that perinatal injury was a reason for congenital Horner syndrome in 16 of 31 (52%) cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other recent studies of clinical distinctions in evaluation include the finding that clinically active elbow extension at 1 month is a significant predictor of a C5-6 lesion [1] and that Horner's syndrome is not proof of a preganglionic C8-T1 lesion [8]. Decreased glenohumeral portion of shoulder movement and increased scapulothoracic contribution to movement in overhead shoulder movements have been described in children with upper plexus palsy [9].…”
Section: Discussionmentioning
confidence: 99%